Case Report: A novel strategy of endoscopic full-thickness resection: single traction combined with pre-clamping - Liu, Jinguo; Xu, Jing; Wang, Li; Gu, Xiaojiang; Zhang, Xuesong; Zhang, Zhou; Zhang, Chi; Yu, Liangliang (Frontiers in Medicine, 2025)
Endoscopic full-thickness resection (EFTR) is an effective, economical, and minimally invasive technique for submucosal tumors (SMTs). However, technical complexity and prolonged operative time remain significant limitations. This study introduces a refined EFTR strategy termed “single traction combined with pre-clamping” in a cohort of 10 patients. The proposed technique demonstrates reduced procedural duration, technical difficulty, and intraoperative risks compared to the conventional approach.